2014
DOI: 10.1002/ptr.5175
|View full text |Cite
|
Sign up to set email alerts
|

α‐Glucosidase Inhibitors from the Stems of Embelia ribes

Abstract: From the ethyl acetate extract of the stems of Embelia ribes (Myrsinaceae), a new alkenylresorcinol, embeliphenol A (1), together with 11 known compounds have been isolated. Their structures were elucidated on the basis of spectroscopic data. All compounds possessed significant α-glucosidase inhibitory activity in a concentration-dependent manner, except for 2 and 9. Compounds 1, 3-6, 8, and 12 showed more potent inhibitory activity, with IC50 values ranging from 10.4 to 116.7 μM, than that of a positive contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(16 citation statements)
references
References 16 publications
1
15
0
Order By: Relevance
“…The methylene proton at δ H 2.67 (H-4) showed HMBC correlations with the δ C 78.4 (C-2), 65.2 (C-3), 156.2 (8a), and 99.0 (5a) in agreement with the substitution pattern in ring C. The HMBC correlations between the proton at δ H 6.88 (H-6′) and δ H 6.67 (H-5′) with that of δ C 78.4 (C-2) and two oxygenated sp 2 vicinal quaternary carbons at δ C 144.6 (C-4′) and 144.7 (C-3′) further support the ABX multiplicity pattern of ring B confirming the exact location of the two hydroxyl groups to be at C-3′ and 4′ positions. Thus, based on the above spectral data the structure of the compound was found to be 3,5,7,3′,4′-pentahydroxyflavan ( 1 ) similar to the previously identified compound epicatechin ( 1 ) with various pharmacological activity [ 11 , 12 ].…”
Section: Resultssupporting
confidence: 68%
“…The methylene proton at δ H 2.67 (H-4) showed HMBC correlations with the δ C 78.4 (C-2), 65.2 (C-3), 156.2 (8a), and 99.0 (5a) in agreement with the substitution pattern in ring C. The HMBC correlations between the proton at δ H 6.88 (H-6′) and δ H 6.67 (H-5′) with that of δ C 78.4 (C-2) and two oxygenated sp 2 vicinal quaternary carbons at δ C 144.6 (C-4′) and 144.7 (C-3′) further support the ABX multiplicity pattern of ring B confirming the exact location of the two hydroxyl groups to be at C-3′ and 4′ positions. Thus, based on the above spectral data the structure of the compound was found to be 3,5,7,3′,4′-pentahydroxyflavan ( 1 ) similar to the previously identified compound epicatechin ( 1 ) with various pharmacological activity [ 11 , 12 ].…”
Section: Resultssupporting
confidence: 68%
“…Compared with those on ingredients 11 , 16 , and 18 , few findings on the antioxidant and anti-inflammatory effects of MPP have been published. It has been reported that MPP displayed inhibitions against 5-lipoxygenase [ 41 ], α -glucosidase [ 42 ], and Mycobacterium tuberculosis H37Rv in vitro [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…17 Alkenylresorcinol, embeliphenol-A has been isolated from ethyl acetate extract of the stems of Embelia Ribes that possess significant α-glucosidase inhibitory activity in a concentrationdependent manner. 18 Embelin, isolated from Embelia Ribes fruits, regulated insulin mediated glucose uptake in epididymal adipose tissue through translocation and activation of GLUT4. 19 Histopathological observations in streptozotocin induced diabetic rats have shown the rejuvenation of β-cells destroyed by following embelin treatment, which indicates the insulinmimicking effect of embelin by regenerating insulin producing cells.…”
Section: Effects Of Embelia Ribes On Elevated Blood Sugarmentioning
confidence: 99%